International Homogenization or the Persistence of National Practices? The Remaking of Industrial Relations in Mozambique - Webster, Edward; Wood, Geoffrey; Brookes, Michael (Relations industrielles / Industrial Relations, 2006)
This paper is the first systematic attempt to provide an overview of industrial relations practices at firm level in Mozambique. Through a nationwide survey of firms, the paper assesses the extent to which specific sets of practices are associated with particular regions, and/or sectors, and explores the relationship between IR practice and national institutional realities. The survey revealed that informalism and autocratic managerialism characterize the practice of employment relations. But it would be mistaken to assume a convergence towards a global systematic archetype of low wage/low skill/low security of tenure set of practices. Instead, the authors conclude, contemporary Mozambique employment relations are an example of external market pressures being channelled and moulded by the persistence of national level realities that stretch back to the colonial era. In the absence of effective institutional mechanisms, familiar conventions are likely to persist because people know how these work in practice.